2014
DOI: 10.1007/s00343-014-3236-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variations in the distribution of macroalgal communities along the Yantai coast, China

Abstract: To explore the impact of environmental variables on macroalgal communities, their temporal and spatial distributions were examined along the Yantai coast, China between April 2010 and March 2011. Macroalgae sampling was conducted monthly at four sites along the coast: Jiahe River estuary, Zhifu Island, Fisherman's Wharf, and Yangma Island. The species composition and abundance, and their relationship with environmental variables were assessed. Along the Yantai coast, 35 macroalgae species were identifi ed, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
2
7
0
1
Order By: Relevance
“…The higher TN of algal tissue of Rhodophyta and Chlorophyta species compared to Phaeophyta species at the four sites along the Yantai coast showed different nitrogen storage between phyla. This is supported by the report that species of Rhodophyta and Chlorophyta had a competitive advantage (Kraufvelin et al, 2010;Han and Liu, 2014). Some filamentous and foliose macroalgal groups showed elevated N content and lower C:N ratios as characterized by simplest structure and/or a higher surface area (Ochoa-Izaguirre and Soto-Jiménez, 2015), which explained U. pertusa in our study showed higher tissue TN at S2, S3 and S4.…”
Section: Factors Related To the Tn And δ 15 N Modification In Algal Tsupporting
confidence: 89%
See 3 more Smart Citations
“…The higher TN of algal tissue of Rhodophyta and Chlorophyta species compared to Phaeophyta species at the four sites along the Yantai coast showed different nitrogen storage between phyla. This is supported by the report that species of Rhodophyta and Chlorophyta had a competitive advantage (Kraufvelin et al, 2010;Han and Liu, 2014). Some filamentous and foliose macroalgal groups showed elevated N content and lower C:N ratios as characterized by simplest structure and/or a higher surface area (Ochoa-Izaguirre and Soto-Jiménez, 2015), which explained U. pertusa in our study showed higher tissue TN at S2, S3 and S4.…”
Section: Factors Related To the Tn And δ 15 N Modification In Algal Tsupporting
confidence: 89%
“…Thus, it was supposed that the growth and absorption of nitrogen of algae at S2, S2 and S4 were limited by PO 4 -P concentrations. This supposition get support from results of Han and Liu (2014) which stated that growth of macroalgae at S1, S3 and S4 were affected by PO 4 -P concentration. Impacts of metabolism to nitrogen and carbon in macrogalgae are species-specific owing to different storage capacity and nutrient requirements for growth (Hanisak and Harlin, 1978;Larned, 1998;Deutsch and Voss, 2006).…”
Section: Factors Related To the Tn And δ 15 N Modification In Algal Tsupporting
confidence: 76%
See 2 more Smart Citations
“…Compared to Dalian Bay and Jiaozhou Bay, Taozi Bay and Sishili Bay are relatively open and mainly influenced by coastal currents. The mean water depths of these two bays are <20 m. Sishili Bay receives nutrients from marine aquaculture operations, wastewater inputs, and harbor pollution (Han and Liu, 2014). Dalian is a major industrial and harbor city with a population of 2.7 million people in an urban area of 2400 km 2 .…”
Section: Study Areamentioning
confidence: 99%